Effect of low level laser on the healing of critical defects filled with or without autogenous bone at 30 and 60 postoperative days: in vivo study - Souza, Lucas Monteiro de Vasconcelos Alves de (2017)
The success of various dental interventions depends on an efficient tissue repair process. In many cases of oral rehabilitation with implants and repair of periodontal bone defects, there is a need for grafting procedures. Autogenous bone remains the gold standard grafting material according to the literature because it presents the characteristics of osteogenesis, osteoconduction and osteoinduction. In order to improve the knowledge about the process of bone repair with autogenous bone and to study the effects of low intensity laser on bone healing, this study aims to evaluate the effect of low intensity laser on critical defect bone healing treated with Autogenous bone (AB) at 30 and 60 postoperative days. 80 adult male rats (Rattus norvegicus, albinus, Wistar) weighing between 250 and 300 g were used. A criticalsize bone defect with a diameter of 5 mm was created in the calvaria of each animal. The animals were randomly divided into 4 groups (n = 20) of treatment: 1) Group C (filled with blood clot), 2) LLL group (low intensity laser - GaAlAs, 780 nm, 100mW, 210J/cm2, 6J), 3) Group AB (autogenous graft), 4) Group ABL (autogenous graft + laser of low intensity) euthanized at 30 and 60 days. An amount of new bone (NBF) was calculated as a percentage of the original defect area. Data were submitted to statistical analysis (ANOVA, Tukey test, p <0.05). Groups AB, LLL and ABL in both periods do not present statistically significant difference of NBF between their self (p > 0.05). There was only statistically significant difference (p < 0.05) when AB, LL and ABL was compared to C group at 30 days and group AB was compared to C at 60 days. In conclusion, the LLL did not present biomudolatory capacity in the increase of NBF. Also, no statistically significant difference was observed when comparing the same technique at times of 30 and 60 days of healing. The LLL group showed greater bone formation compared with C group only in 30-days analysis, suggesting capacity of accelerate the bone formation.